GC-MS ANALYSIS, ADME TOXICITY and in silico STUDIES OF SOME ISOLATED COMPOUNDS FROM Melastoma malabathricum LEAVES AGAINST SPLA2 INHIBITION (Applied Biological Research, 2023)
The bioactive components of Melastoma malabathricum leaves and the  chemical compositions of ethanol-based M. malabathricum leaf extract were  studied using gas chromatography-mass spectrometry (GC-MS) analysis.  Twelve compounds obtained were: phthalic acid hept-4-yl isobutyl ester,  oleic acid, n-hexadecanoic acid, melezitose, hexadecanoic acid methyl ester,  hexadecanoic acid ethyl ester, D-mannose, 9,10 secocholesta-5,7,10(19) triene-3,24,25, triol, (3β,5Z,7E), 2-myristynoyl pantetheine, propanamide,  3-[3,5di(tetra-butyl)-4hydroxyphenyl]-N-(2hydroxyethyl), cholesta 4,6- dien-3-ol and desulphosinigrin. These compounds were characterized and  analyzed for sPLA2 inhibition by molecular docking using the standard  inhibitors. Among these, 2-myristynoyl pantetheine showed better inter actions with sPLA2IIA enzyme with ‘e’ value of -8.62 (PubChem id:  535560), followed by desulphosinigrin (-7.19) and D-mannose (-4.96).  ADME toxicity studies proved that 2-myristynoyl pantetheine is better for  in vivo administration. The 2-myristynoyl pantetheine was found to exhibit  anti-inflammatory activity.
Keywords: ADME toxicity; GC-MS; Melastoma malabathricum; molecular docking; phytocomponents; sPLA2 inhibition